Zanim urodzi się słowo (Z doświadczenia rosyjskiej szkoły sztuki aktorskiej) - Zaorska, Magdalena (Acta Polono-Ruthenica, 2010)
This article deals with the upbringing of an actor, according to the principles of Stanislavsky, in which verbal communication in the first months of training recedes into the background to create a space for dialogue based on students activities. Please note that the text is focused on these pro- cesses which precede the vocal act of the actor. The author shows the essential components of tra- ining an actor, which we have to deal with during exercising the elementary tasks of acting in the first year at drama school. The article exposes the role of the perfect (spiritual) need for recogni- tion and highest task in the educational process of the actor. The psychophysiological interpreta- tion of physical actions method occupies an important position in the text, as well as its interpre- tation in the Soviet and Russian theatre pedagogy. The first part of the article was devoted to theoretical aspects of education of the actor, and the second author confronts the practice of the- oretical assumptions and presents exercises and etudes that are canvas of Stanislavsky school.